Cerebral metabolism following traumatic brain injury: new discoveries with implications for treatment - Brooks, George A.; Martin, Neil A. (Frontiers in Neuroscience, 2015)
Because it is the product of glycolysis and main substrate for mitochondrial respiration, lactate is the central metabolic intermediate in cerebral energy substrate delivery. Our recent studies on healthy controls and patients following TBI using [6,6-2H2]glucose and [3-13C]lactate, along with cerebral blood flow and arterial-venous (jugular bulb) difference measurements for oxygen, metabolite levels, isotopic enrichments and 13CO2 show a massive and previously unrecognized mobilization of lactate from corporeal (muscle, skin and other) glycogen reserves in TBI patients who were studied 5.72.2 days after injury at which time brain oxygen consumption and glucose uptake (CMRO2 and CMRgluc, respectively) were depressed. By tracking the incorporation of the 13C from lactate tracer we found that gluconeogenesis (GNG) from lactate accounted for 67.1%, of whole-body glucose appearance rate (Ra) in TBI, which was compared to 15.2% in healthy, well-nourished controls. Simultaneous cerebral exchange measurements showed that fractional lactate extraction (FExlac, 12.5%) was undiminished following TBI, and as in controls close to 100% of lactate taken up was oxidized in TBI. Hence, 68% of the carbohydrate energy (CHO = glucose + lactate) taken up and used by the injured brain came from lactate, either directly by vascular delivery of lactate (9%), or indirectly by GNG from lactate and its contribution to CMRgluc (59%). By comparison, lactate contributed 25% of the CHO energy taken up by brains of healthy postabsorptive control subjects, either directly (12%), or indirectly (13%). As such, a Lactate Shuttle mechanism makes substrate available, both directly and indirectly for the body and brain in healthy individuals and TBI patients. Because CMRlac was maintained, whereas CMRgluc was suppressed following TBI, our recent results support use of exogenous lactate-containing formulations as means to augment nutritive support to the injured brain.